2008
DOI: 10.1016/j.peptides.2008.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Peptides containing membrane-interacting motifs inhibit herpes simplex virus type 1 infectivity

Abstract: Herpes simplex virus (HSV) membrane fusion represents an attractive target for anti-HSV therapy. To investigate the structural basis of HSV membrane fusion and identify new targets for inhibition, we have investigated the different membranotropic domains of HSV-1 gH envelope glycoprotein. We observed that fusion peptides when added exogenously are able to inhibit viral fusion likely by intercalating with viral fusion peptides upon adopting functional structure in membranes. Interestingly, peptides analogous to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 61 publications
2
57
0
Order By: Relevance
“…If aggregation occurred only in the water but not in the bilayer phase, the opposite course of the isotherms should be expected as follows: a steep rise at the origin, followed by pronounced flattening; thus, the shape of the isotherms could be interpreted as reflecting a process whereby peptides first incorporate into the membrane and then aggregate within. Moreover, there was no evidence of aggregation in water at the concentration used in this experiment (0.1 M); some indication of aggregation was observed at higher concentrations from native PAGE and circular dichroism studies (57). In our isotherms, the total extent of incorporation (X b *) slowly increases until a critical concentration is reached, where massive internal aggregation apparently starts to develop.…”
Section: Characterization Of Binding Isotherms and Determination Of Pmentioning
confidence: 58%
“…If aggregation occurred only in the water but not in the bilayer phase, the opposite course of the isotherms should be expected as follows: a steep rise at the origin, followed by pronounced flattening; thus, the shape of the isotherms could be interpreted as reflecting a process whereby peptides first incorporate into the membrane and then aggregate within. Moreover, there was no evidence of aggregation in water at the concentration used in this experiment (0.1 M); some indication of aggregation was observed at higher concentrations from native PAGE and circular dichroism studies (57). In our isotherms, the total extent of incorporation (X b *) slowly increases until a critical concentration is reached, where massive internal aggregation apparently starts to develop.…”
Section: Characterization Of Binding Isotherms and Determination Of Pmentioning
confidence: 58%
“…Detailed morphological, cultural, and microscopic characters including growth rate of the colony, colony diameter, color of mycelium (dorsal and ventral), texture of colony, type of mycelium, presence or absence of conidia/spores, shape of conidia/ spores, and shape of conidia alone were recorded with the help of standard books and keys used for identification of fungi. 34 These fungal species were confirmed as Alternaria species, F. oxysporum, Curvularia species, C. indicum, and Phoma species ( Figure 1A) recovered from the leaves of Dryopteris species, M. paradisiaca, C. roseus, and S. bryopteris.…”
Section: Isolation and Identification Of Fungi From Plantsmentioning
confidence: 73%
“…Different methods were used to treat the cell monolayers to assess the effect of AgNPs on inhibition of HSV-1, HSV-2, and HPIV-3 infectivity. 34 …”
Section: Assessment Of Antiviral Activitymentioning
confidence: 99%
“…10,11 This peptide has proved to exhibit exceptional vector properties 9 and has been shown to be essentially internalized by a nonendocytic pathway avoiding endosomal entrapment. 7,[12][13][14][15][16][17] In recent studies, it was also shown to be able to cross the blood-brain barrier in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%